Designing A Pathogen-Focused Study To Address The High Unmet Medical Need Represented By Carbapenem-Resistant Gram-Negative Pathogens – The International, Multicenter, Randomized, Open-Label, Phase 3 CREDIBLE-CR Study - Bassetti M; Ariyasu M; Binkowitz B; Nagata TD; Echols RM; Matsunaga Y; Toyoizumi K; Doi Y (Infection and Drug Resistance, 2019)
Matteo Bassetti,1,2 Mari Ariyasu,3 Bruce Binkowitz,4 Tsutae Den Nagata,3 Roger M Echols,5 Yuko Matsunaga,4 Kiichiro Toyoizumi,4 Yohei Doi6 1Infectious Diseases Clinic, Department of Medicine, University of Udine and Azienda Sanitaria Universitaria Integrata, Udine, Italy; 2Department of Health Sciences, University of Genoa, Genoa, Italy; 3Shionogi & Co., Ltd., Osaka, Japan; 4Shionogi Inc., Florham Park, NJ, USA; 5Infectious Disease Drug Development Consulting, LLC, Easton, CT, USA; 6Division of Infectious Diseases, University of Pittsburgh School of Medicine, Pittsburgh, PA, USACorrespondence: Matteo BassettiClinica di Malattie Infettive, Azienda Sanitaria Universitaria Integrata di Udine, Presidio Ospedaliero Universitario Santa Maria della Misericordia, Piazzale Santa Maria della Misericordia 15, Udine 33010, ItalyTel +390432559353Email matteo.bassetti70@gmail.comAbstract: Carbapenem-resistant (CR) Gram-negative infections, including those caused by Enterobacteriaceae and the non-fermenters, represent the greatest unmet need for new effective treatments. The clinical development of new antibiotics for the treatment of CR infections is challenging and should focus on the individual pathogens irrespective of the infection site. However, the drug approval pathway is generally infection-site specific and rarely includes such drug-resistant pathogens. To overcome this limitation, a streamlined clinical development program may include a pathogen-focused clinical study, such as the CREDIBLE-CR study, to meet the expectations of some health authorities (ie, the European Medicines Agency [EMA]) and the medical community. Cefiderocol is a novel siderophore cephalosporin designed to target CR pathogens, including CR strains of Enterobacteriaceae (CRE), Pseudomonas aeruginosa, Acinetobacter baumannii, and also Stenotrophomonas maltophilia, which is intrinsically CR. The CREDIBLE-CR study was planned to evaluate cefiderocol in patients with CR Gram-negative infections regardless of species or infection-site source. Rapid diagnostic testing and/or selective media were provided to facilitate detection of CR pathogens to rapidly enroll patients with nosocomial pneumonia, bloodstream infection/sepsis, or complicated urinary tract infection. Patients were randomized 2:1 to receive cefiderocol or best available therapy. There were no pre-specified statistical hypotheses for this study, as the sample size was driven by enrollment feasibility and not based on statistical power calculations. The objective of the CREDIBLE-CR study was to provide descriptive evidence of the efficacy and safety of cefiderocol for the target population of patients with CR infections, including the non-fermenters. The CREDIBLE-CR study is currently the largest pathogen-focused, randomized, open-label, prospective, Phase 3 clinical study to investigate a new antibiotic in patients with CR Gram-negative infections. Here we describe the design of this pathogen-focused study and steps taken to aid patient enrollment into the study within an evolving regulatory environment.ClinicalTrials.gov registration: NCT02714595.EUDRA-CT registration: 2015-004703-23.Keywords: best available therapy, cefiderocol, carbapenem resistance, pathogen-focused study design, rapid diagnostics, streamlined/limited clinical development